Implementation of OJK Regulation Number 43/Pojk.04/2015 Concerning Code of Conduct for Investment Managers Against Stock Price Manipulation in the Case of PT. Jiwasraya - Rian Rimba Morenties; Gunardi Lie; Moody Rizqy Syailendra Putra (CV. Rayyan Dwi Bharata, 2023)
The capital market is one of the instruments in investing. The Capital Market or what is commonly called the capital market can provide opportunities for the public to gain profits. However, the capital market also plays an active role in improving domestic economic conditions. Capital Market or capital market is an activity related to the public offering and trading of securities, public companies related to securities issued, as well as institutions and professions related to securities. The Capital Market or capital market acts as a liaison between investors and companies and government agencies through long-term trading of instruments such as bonds, stocks and others. According to Article 1 paragraph 13 of Law Number 8 of 1995 concerning Capital Markets, the definition of capital markets is activities related to public offerings and securities trading, public companies related to the securities they issue, as well as institutions and professions related to securities.